PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM PADA SUB SEKTOR TEKSTIL & GARMEN - Leonardo, Meychester; Kharismar, Emir (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to test and analyze empirically the effect of the current ratio, cash ratio, return on equity, net profit margin, and firm size on stock returns. The objects studied are companies that are in the textile garment sub-sector and are listed on the Indonesia Stock Exchange during the period 2012 to 2019. The sample selection technique uses purposive sampling so that there are 6 companies that meet the criteria as samples. Then the data were analyzed using multiple linear regression.The results of this study are the current ratio has an positive effect on stock returns. This shows that the higher the company's liquidity level, the better the company's performance and this makes investors more interested in buying the company's shares, so that stock returns can increase. While the cash ratio, return on equity, net profit margin, and firm size have no effect on stock returns.